Automated Feature Description Of Renal Size Using Image Processing - Nur Farhana Rosli; Musab Sahrim; Wan Zakiah Wan Ismail; Irneza Ismail; Juliza Jamaludin; Sharma Rao Balakrishnan (Penerbit UTHM, 2024)
Volume: 10 No: 1